2020
DOI: 10.1002/adma.201906712
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical 3D Patterns with Dynamic Wrinkles Produced by a Photocontrolled Diels–Alder Reaction on the Surface

Abstract: Three‐dimensional (3D) reconfigurable patterns with dynamic morphologies enable the on‐demand control of surface properties, such as optical, wetting, and adhesive properties, to achieve smart surfaces. Here, a simple yet general strategy is developed for fabricating 3D patterns with reversible wrinkles on the surface, in which a Diels–Alder (D‐A) reaction in the top layer, which consists of a reversible cross‐linked polymer network composed of a furan‐containing copolymer (PSFB) and bismaleimide (BMI), can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 49 publications
0
44
0
Order By: Relevance
“…The morphology of the wrinkles is parallel to each other and perpendicular to the unexposed regions (marked as II), which might be resulted from boundary effect. [48] After the second UV irradiation without mask, labyrinth patterns formed in the region II with a much smaller wavelength (λ) of 35 µm and bigger amplitude (A) of 2.8 µm (Figure 3c,d) comparing with the patterns in region I. It might be ascribed to the boundary effect of the region I.…”
Section: Mechanism For Hierarchical Patterns Of Self-wrinklingmentioning
confidence: 90%
“…The morphology of the wrinkles is parallel to each other and perpendicular to the unexposed regions (marked as II), which might be resulted from boundary effect. [48] After the second UV irradiation without mask, labyrinth patterns formed in the region II with a much smaller wavelength (λ) of 35 µm and bigger amplitude (A) of 2.8 µm (Figure 3c,d) comparing with the patterns in region I. It might be ascribed to the boundary effect of the region I.…”
Section: Mechanism For Hierarchical Patterns Of Self-wrinklingmentioning
confidence: 90%
“…Beyond the wrinkling of large-size uniform film bonded on elastic substrate, recently, a series of studies have revealed differently post-wrinkle morphologies in systems composed of patterned stiff films on soft substrates [111][112][113][114][115][116][117][118][119]. When the length scale of the pattern is comparable to the wavelength of wrinkles, stress localization near the pattern arises under compression.…”
Section: Planar Substratesmentioning
confidence: 99%
“…The feature size, geometry, and spacing are all demonstrated to have important effect on the wrinkling and post-wrinkle morphologies of patterned films [ 111 , 114 , 116 , 118 ]. For example, the preformed pattern can act as novel boundary to direct surface wrinkling for controllable fabrication of hierarchical wrinkling patterns with precise orientation [ 113 , 119 ]. Besides, stress localization near the patterned region triggers the decrease of the threshold compression for the onset of various wrinkling morphologies.…”
Section: Mechanics Behind the Wrinklesmentioning
confidence: 99%
“…[23,30] Surface wrinkling is ubiquitous in our daily life. [31][32][33][34][35] In nature, dried fruits, leaves, and aged skins present wrinkling surfaces in response to internal/external changes. [36,37] Inspired by the distinct functions and mechanisms of biological wrinkle structures, a lot of experimental and theoretical studies have been conducted to understand and modulate various wrinkle patterns induced by thermal, mechanical, optical, or chemical stimuli on artificial materials.…”
mentioning
confidence: 99%